Pharmacological activities of Alangium salviifolium (L.f.) Wangerin extracts - Karunya, S.; Srinivasan, P.; Balakrishnan, V. (Current Botany, 2025)
Tribal communities traditionally use Alangium salviifolium raw extracts to treat skin diseases. Inspired by tribal knowledge and the understanding that some skin conditions may be linked to liver health, the study explored the potential of A. salviifolium for treating liver pathogen infections. This study evaluates methanolic leaf, fruit, and seed extracts for their potential therapeutic effects against liver-related pathogens and conditions, aiming to explore their usefulness in treating liver diseases. The extracts were evaluated for antibacterial activity using the agar well diffusion method. Each bacterial strain was tested with a different control antibiotic: Escherichia coli (Chloramphenicol), Streptococcus mutans (Amikacin), Salmonella typhi (Ciprofloxacin), and Klebsiella pneumonia (Co-trimoxazole). The leaf extracts showed the strongest antibacterial inhibition at both concentrations, followed by moderate inhibition by the fruit and seed extracts. Antifungal activity was assessed using the Kirby–Bauer disk diffusion method against C. albicans, C. tropicalis, C. parapsilosis, and C. glabrata, with Fluconazole as the control. In the antifungal assays, each extract displayed a distinct performance against the tested fungal strains. The anti-inflammatory activity was analyzed using the bovine serum albumin denaturation assay, which showed IC50 values of 784 μg/mL for the leaf extract, 417 μg/mL for the fruit extract, and 354 μg/mL for the seed extract, with diclofenac as the control. Anticancer activity, tested on HepG2 cells using the MTT assay, showed IC50 values of 109.7 μg/mL for the fruit extract, 93.9 μg/mL for the leaf extract, and 49.5 μg/mL for the seed extract. The results indicate that the seed extract exhibits the most potent broad-spectrum bioactivities. Further in vivo and clinical studies are warranted to confirm therapeutic efficiency and safety for liver disease treatment.